Development of Guo Tourism Village through the Restoration of Ba Atok Bridge as an Effort to Preserve Minangkabau Cultural Wisdom - Nurhamidah Nurhamidah; Ahmad Junaidi; Rudy Ferial; Masril Syukur (Warta Pengabdian Andalas, 2024)
Bridge infrastructure is critical in connecting one region with other areas separated by rivers or ravines. In Minangkabau, a type of bridge is built using the Ba Atok Bridge roof. This bridge structure is characterised by pointed roof-like buffalo horns, where the Minangkabau people are known as Gonjong. The remaining Ba Atok Bridge is located in Padang City, specifically in Guo Village, Jalan Lubuak Tampuruang, Kuranji Village, Kuranji District, Padang City, with a bridge length of 16 meters. The community needs the Ba Atok Bridge as a bridge to cross the river to gardens, schools, madrasas, mosques, and other villages. Its unique shape has charm, and this is one of the cultural heritage assets that must be maintained as a characteristic bridge between the nuances of traditional Minangkabau culture. Therefore, the Community Service Team of the Faculty of Engineering, Andalas University, is also collaborating with the Tourism Awareness Group (POKDARWIS), which also has the same initiative, namely carrying out bridge restoration with traditional Minangkabau cultural nuances. Restoration begins with identifying damage, discussing it with community groups, making an architectural design, submitting a proposal to Bank Nagari, and repairing the bridge's upper frame. The Ba Atokini bridge restoration activities impact crossing access and have become characteristic of the Guo Tourism Village, which POKDARWIS manages.